Plasmonic enhancement of infrared vibrational signals: nanoslits versus nanorods - Huck, Christian; Vogt, Jochen; Sendner, Michael; Hengstler, Daniel; Neubrech, Frank; Pucci, Annemarie (ACS photonics, 2015)
We report on systematic investigations of plasmonically active nanoslits as a beneficial substrate for surface-enhanced infrared absorption (SEIRA). Arranged in arrays, nanoslits with the proper geometry feature strong nanorod-like resonances in the infrared spectral range, as predicted by Babinet’s principle for the same geometrical dimensions. SEIRA enhancement as studied with a thin self-assembled molecular layer of octadecanethiol reaches the values obtained with nanorods if the slit geometry is optimized. We show by systematically examining the important parameters that the slit width has an especially strong influence on the near-field intensity and therefore on the SEIRA signal. Furthermore, the transversal and longitudinal couplings of nanoslits are studied. Compared to nanorod arrays, a stronger influence of the array periodicities on the plasmonic excitations is observed, which indicates coupling via surface plasmon polaritons. So the array periodicity could be further optimized toward higher SEIRA signals. Our results give access to general design rules for sensing applications based on the use of inverse nanostructures.
Gesehen am 02.06.2020